PENERAPAN MODEL INSTRUKSIONAL 4EX2 UNTUK MEREDUKSI JUMLAH PESERTA DIDIK YANG MISKONSESPSI PADA MATERI GHS - Meilisa, Meilisa; Sahala S, Stepanus; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study investgated the effectiveness of instructional model Engage, Explore, Explain, Extend (4Ex2) to reduce the number of students who have misconceptions on simple harmonic motion at MAN 2 Pontianak. This research is pre-experimental research with one group pre-test post-test design with a total sample of 36 students from class XI MIA 2. The diagnostic test which consist of 10 multiple choices with open reason used to identification studentâ€™s misconception. Based on the analysis of diagnostic data using the McNemar test, there was a significant students conceptual change (x2count = 15,75; df = 1; ) after instruction. The use of Instructional Model 4Ex2 effective to reduce the number of students who are misconceptions in medium category (< g > = 0,63). This research is expected to be used as alternative remediation activities to reduce misconceptions in a learning processKeywords: Miskonsepsi, Model Instruksional 4Ex2, Getaran HarmonisÂ